HEALTH MANAGEMENT IN WILD TURKEY RESTORATION PROGRAMS - Terry E. Amundson (Wildlife Society Bulletin)
Abstract: An important consideration for introduction of wildlife populations is the risk of disease introduction or dissemination. During the mid‐1970s, a wild turkey restoration program was begun in Wisconsin. The objective of this program was to reestablish a naturally reproducing population of wild turkeys, while minimizing the potential for transmission of avian pathogens to other wild gamebird populations or domestic turkey flocks. A program of health inspection and disease monitoring was implemented to test wild turkeys brought into Wisconsin for release. Serologic evidence of Mycoplasma spp. was detected in a significant number of imported turkeys. The significance of these and other findings of mycoplasmosis in wild and game farm turkeys prompted the development of detailed guidelines for disease monitoring in wild turkey relocation and restoration programs. These guidelines recommend health inspections of representative turkeys from prospective trap sites prior to a relocation program. Disease monitoring, including field testing of sera for Mycoplasma spp. and Salmonella spp. was further recommended for all imported turkeys prior to release with subsequent testing for additional avian pathogens by diagnostic laboratories suggested, depending on availability of technical and financial support.